2018
DOI: 10.1177/2333794x18811795
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Development in Children Born to HIV-Infected Mothers: Perspectives From Kenyan Clinical Providers and Caregivers

Abstract: Objective. To understand the perspectives of clinical providers and caregivers regarding early childhood development (ECD) in children born to HIV-infected mothers in Kenya. Methods. This was a qualitative study of provider and caregiver perspectives on ECD at 5 Kenyan HIV clinics, using semistructured interviews and focus group discussions. Constant comparison and triangulation methods were employed to elucidate the concepts of ECD. Results. Twenty-five providers and 67 caregivers participated. While provider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For children linked to multiple caregivers, the mother was preferentially selected, followed by the father. In western Kenya and other contexts in sub‐Saharan Africa, mothers are commonly the primary caregivers for children living with HIV . We elected to restrict our sample to those caregiver–child VLs that occurred within 90 days of one another, as we assumed this to be a reasonable period in which a temporal association between caregiver–child viral suppression could be evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…For children linked to multiple caregivers, the mother was preferentially selected, followed by the father. In western Kenya and other contexts in sub‐Saharan Africa, mothers are commonly the primary caregivers for children living with HIV . We elected to restrict our sample to those caregiver–child VLs that occurred within 90 days of one another, as we assumed this to be a reasonable period in which a temporal association between caregiver–child viral suppression could be evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…A third hypothesis is that certain aspects of development are more adaptive and highly prioritized in settings like Kenya compared to the U.S. but are not measured with assessments like the Bayley-3, thereby resulting in a lower score. As a general example of expectation differences between cultures, we previously found that Kenyan clinical providers were concerned when children were not walking independent by 12 months of age ( 50 ), whereas, the U.S. Centers for Disease Control expects that most children will not walk independently until 18 months ( 51 ). As with all assessments, the items are evaluated are on the constructs deemed important by the test developers, which may introduce scoring bias.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies, many involving the local community, informed the study design and consent process for this study. [42][43][44][45] At study completion, we will hold a series of meetings among healthcare providers caring for the recruited population (those who work within the MTRH antenatal and postnatal clinics and wards), as well as local village elders and chiefs. During these meetings, we will disseminate the results of the study.…”
Section: Patient and Public Involvementmentioning
confidence: 99%